2004
DOI: 10.1016/j.jcrs.2004.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Adverse clinical consequences of neodymium:YAG laser treatment of posterior capsule opacification

Abstract: Purpose: To evaluate the clinical consequences of complications from neodymium:YAG (Nd:YAG) laser capsulotomy for posterior capsule opacification (PCO) over the lives of cataract patients.Setting: CHU de Caen, Caen, France. Methods: A model was constructed to estimate the lifetime clinical consequences of postoperative PCO treated by Nd:YAG laser capsulotomy. The probability of death was modeled from French mortality tables as a polynomial function of sex and age. The probability of becoming blind was modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 54 publications
2
60
0
4
Order By: Relevance
“…Furthermore, it has been shown that the incidence of retinal detachment and cystoid macular oedema after Nd:YAG laser capsulotomy is uncommon in eyes that have previously undergone phacoemulsification and in-the-bag implantation of an IOL. [19][20][21][22] These findings suggest that the incidence of the adverse effects may not differ markedly between eyes with a small capsulotomy and those with a large capsulotomy.…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, it has been shown that the incidence of retinal detachment and cystoid macular oedema after Nd:YAG laser capsulotomy is uncommon in eyes that have previously undergone phacoemulsification and in-the-bag implantation of an IOL. [19][20][21][22] These findings suggest that the incidence of the adverse effects may not differ markedly between eyes with a small capsulotomy and those with a large capsulotomy.…”
Section: Resultsmentioning
confidence: 80%
“…PCO impedes vision and requires YAG‐laser treatment to remove the fibrotic mass to clear the visual axis. However, laser treatment could have unintended ill effects, albeit at a low occurrence; these effects can include retinal detachment, macular edema, corneal edema, and displacement of intraocular lens (Billotte & Berdeaux, 2004). Thus, efforts are being made to inhibit PCO development.…”
Section: Introductionmentioning
confidence: 99%
“…Although various methods to treat PCO have been attempted, neodymium yttrium-aluminum-garnet (YAG) capsulotomy is yet the gold standard because it is non-invasive, can be applied rapidly under polyclinic conditions, and has a high success rate. However, some complications may occur after YAG capsulotomy (1)(2)(3) . Changes in intraocular pressure are frequently observed following YAG capsulotomy (4) and may have an impact on the choroid, which is sensitive to fluctuations inintraocular pressure (IOP).…”
Section: Introductionmentioning
confidence: 99%